(untitled) (Journal of Hama University, 2022)
Aim of The Study: the aim of the research is to Study the effect of in-office bleaching on shear bond strength of orthodontic metal brackets luted with RMGIC, and to determine the effect of 10% sodium ascorbate (SA) to reverse the reduced shear bond strength (SBS) of orthodontic bracket after in-office bleaching. Materials and Methods: A total of 80 maxillary first premolar teeth were randomly divided into 4 groups as follow (n=20) group A -control (no bleaching), group B (Bleaching + bonding immediately), group C (bleaching + waiting for one week), group D (bleaching + 10% sodium ascorbate (SA)). The brackets were bonded with the resin-modified glass ionomer cement RMGIC, SBS testing was performed using universal testing machine, and the adhesive remnant index (ARI) was examined using metallurgical microscope after debonding. The SBS data were analyzed by analysis of variance one way (Anova) and Post Hoc Tests (Bonferroni) .For the ARI, the Kruskal-Wallis test was performed and Mann-Whitney tests. Results: There was significant SBS difference (p <0.05) between various groups. The group A without bleaching showed higher SBS (11.73±2.21 MPa) compared to others, while SBS in the group B was significantly lower SBS (7.18± 2.04 MPa) than other groups. For ARI the failure of orthodontic brackets bonded occurred at the enamel-adhesive interface. Conclusion: The SBS of brackets luted with RMGIC after in-office bleaching reached to clinically acceptable levels up to 70% and the application of 10% sodium ascorbate (SA) as an antioxidant or waiting one week after dental bleaching was effective in reversing the reduced shear bond strength of orthodontic brackets after bleaching.